2020
DOI: 10.1002/dvdy.254
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of the epididymis from Plag1 deficient mice suggests dysregulation of sperm maturation and extracellular matrix genes

Abstract: Background: The transcription factor pleomorphic adenoma gene 1 (PLAG1) is required for male fertility. Mice deficient in PLAG1 exhibit decreased sperm motility and abnormal epididymal tubule elongation and coiling, indicating impaired sperm maturation during epididymal transit. However, the downstream transcriptomic profile of the Plag1 knockout (KO; Plag1 −/−) murine epididymis is currently unknown. Results: In this study, the PLAG1-dependent epididymal transcriptome was characterised using RNA sequencing. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 74 publications
1
7
0
Order By: Relevance
“…Ectopic PLAG1-S significantly altered the expression of 543 genes (supplemental Table 4; Figure 4C ). Consistent with its understood function as a transcription activator, 60% of the 291 upregulated genes are proximally bound by PLAG1-S. Thirty percent of downregulated genes are also directly bound, which similarly to other recent publications, 60 suggests an underappreciated role for PLAG1-S in negative regulation of gene expression. Gene set enrichment analysis (GSEA) revealed that coordinated pathway-level changes are dominated by negative enrichments (supplemental Table 6).…”
Section: Resultssupporting
confidence: 82%
“…Ectopic PLAG1-S significantly altered the expression of 543 genes (supplemental Table 4; Figure 4C ). Consistent with its understood function as a transcription activator, 60% of the 291 upregulated genes are proximally bound by PLAG1-S. Thirty percent of downregulated genes are also directly bound, which similarly to other recent publications, 60 suggests an underappreciated role for PLAG1-S in negative regulation of gene expression. Gene set enrichment analysis (GSEA) revealed that coordinated pathway-level changes are dominated by negative enrichments (supplemental Table 6).…”
Section: Resultssupporting
confidence: 82%
“…With the advancement of sequencing technologies ( Wong et al, 2020 ; Wu et al, 2021a ; Zhao et al, 2021a ; Liu et al, 2022b ), a greater understanding of the molecular mechanisms underlying epididymal function has been achieved. The significance of the epididymis in male reproductive biology has garnered increasing attention.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, the dynamic alterations of the gonadal extracellular matrix have been observed from puberty stage to sexual mature stage [ 22 , 23 ]. Since the extracellular matrix is a reservoir for growth factors and bioactive molecules that orchestrate cell signaling, functions, properties, and morphology, it is naturally considered as a key player in modulating epididymal tissue homeostasis and sperm maturation [ 24 , 25 ]. Some DEGs not only affect extracellular matrix construction but also associate with sperm physiological function were found (Fig.…”
Section: Discussionmentioning
confidence: 99%